Kapasitas Aerobik Maksimal Melalui Tes Cooper 12 Menit Pada Siswa Kelas X Mia SMA Negeri 31 Maluku Tengah - Umasugi, Gabril Fagil; unmehopa, Wilhelmina; Tahapary, Johni Melvin (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2024)
The importance of maximal aerobic capacity fitness in daily activities is undoubtedly the higher the level of health, the better aerobic capacity fitness will be. Good aerobic capacity fitness can support activities in daily life. Having good aerobic capacity, people will be able to carry out daily activities for a longer time than people with low aerobic endurance fitness. Maximum aerobic endurance can be interpreted as a person's ability to carry out daily life without causing excessive fatigue and still have the ability to fill other light jobs. Especially for class X mia students, the use of aerobic endurance is very important, because maximum aerobic endurance is the main capital for a class X Mia student at SMA Negeri 31 Central Maluku to help achieve achievements and make endurance movements that are in accordance with their abilities. The aim of this study was to determine the maximum aerobic endurance level of students and students of class X Mia SMA Negeri 31 Central Maluku. The method used in this research is descriptive quantitative method through test instruments. The population in this study amounted to 28 students and students aged 13-15 years. The sample used was the entire population, namely 28 female students and students aged 13-15 years according to the 12-minute Cooper test norm for maximum aerobic endurance Rizal, 2019. Based on the results data processing of the 12-minute Cooper test results for aerobic endurance and the overall sample was in the very poor or very poor category, the 12-minute running test became a weakness for students of Class X Mia SMA Negeri 31 Central Maluku with a very poor or very poor percentage due to lack of Aerobic endurance exercise and body mass index and muscle mass of class X Mia students are different from muscle mass and body mass of students who are dominant with the hormone testosterone. This also makes the body mass of students and students better than students who do not do sports activities well, because of the lack of aerobic endurance in students and many students who do not do sports activities well